1984
DOI: 10.1016/0022-2313(84)90137-6
|View full text |Cite
|
Sign up to set email alerts
|

Concentration quenching in ND-doped glasses

Abstract: This is • preprint of a piper intended for publication in a journal or proceedings. Since changes ma> be made before publication, this preprint is made available with the un derstanding that it will not he cited or reproduced without the permission of the author Mtttf* DISCLAIMER This document was prepared as an account of work sponsored by an agency of the L'nited Stales Government.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…migration of the excitation energy, as demonstrated in Nddoped phosphate glasses or silica glasses. 13,14 Moreover, a decrease of the PL intensity due to the solubility limit of Nd in SnO 2 cannot be rejected. The evolution of the PL spectra with the doping level is also correlated to the PL band at around 600 nm.…”
mentioning
confidence: 99%
“…migration of the excitation energy, as demonstrated in Nddoped phosphate glasses or silica glasses. 13,14 Moreover, a decrease of the PL intensity due to the solubility limit of Nd in SnO 2 cannot be rejected. The evolution of the PL spectra with the doping level is also correlated to the PL band at around 600 nm.…”
mentioning
confidence: 99%
“…6, the calculated oscillation by assuming Sm-Sm scattering shows a satisfactory agreement with the back-transformed oscillation. It can be concluded that, therefore, Sm atoms agglomerate and form oxide cluster at higher concentrations, which is the reason for the concentration quenching (15,16).…”
Section: [ Gelmentioning
confidence: 99%
“…Manuscript received Oct. 31, 1989. This was in part Paper 585 and Paper 586 presented at the Hollywood, FL, Meeting of the Society, Oct. [15][16][17][18][19][20] 1989.…”
Section: Acknowledgmentsmentioning
confidence: 99%